PENYULUHAN MANAJEMEN KEUANGAN PADA KELOMPOK MASYARAKAT CINA BENTENG SEWAN RAWA KUCING - Presly Darmawan (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
Financial management plays an important role in the business development of MSME actors. One of the basic financial management that needs to be understood by business actors is managing finances properly and correctly. This Community Service activity is carried out to assist in improving the financial management of community financial literacy, especially MSMEs in Sewan Rawa Kucing Tangerang. The method of implementation is in the form of material distribution, lectures, and discussions/debriefings which are conducted offline. The conclusions obtained from this activity show that most MSME actors and the community in Sewan Rawa Kucing still have a low level of financial literacy, however, after carrying out this community service activity, participants' knowledge of the basic concepts of financial management has improved.